Influence of plant genotype and soil on the cotton rhizosphere microbiome - Yang, Chuanzhen; Yue, Hongchen; Ma, Zheng; Feng, Zili; Feng, Hongjie; Zhao, Lihong; Zhang, Yalin; Deakin, Greg; Xu, Xiangming; Zhu, Heqin; Wei, Feng (Frontiers in Microbiology, 2022)
Rhizosphere microbial communities are recognized as crucial products of intimate interactions between plant and soil, playing important roles in plant growth and health. Enhancing understanding of this process is a promising way to promote next green revolution by applying the multifunctional benefits coming with rhizosphere microbiomes. In this study, we propagated eight cotton genotypes (four upland cotton cultivars and four sea-land cotton cultivars) with varying levels of resistance to Verticillium dahliae in three distinct soil types. Amplicon sequencing was applied to profile both bacterial and fungal communities in the rhizosphere of cotton. Results revealed that soil origin was the primary factor causing divergence in rhizosphere microbial community, with plant genotype playing a secondary role. Shannon and Simpson indices revealed no significant differences in the rhizosphere microbial communities of Gossypium barbadense and G. hirsutum. Soil origin accounted for 34.0% and 59.05% of the total variability in the PCA analysis of the rhizosphere bacterial and fungal communities, respectively; while plant genotypes within species only contributed for 1.1% to 6.6% of the total variability among microbial population. Similar results were observed in the Bray-Curtis indices. Interesting, the relative abundance of Acidobacteria phylum in G. barbadense was greater in comparison to G. hirsutum. These findings suggested that soil origin and cotton genotype modulated microbiome assembly with soil predominantly shaping rhizosphere microbiome assembly while host genotype slightly tuned this recruitment process by changing abundance of specific microbial consortia.